Mentorship in psychiatry: A brief report of designing and implementing a program for residents at university of medical sciences - Roya Vaziri-Harami; Mojgan Khademi; Alireza Shamsi; Seyedeh Morvarid Neishabouri; Shiva Eiliaei (Journal of Education and Health Promotion)
Background: Clinical education is crucial; however, students often find it challenging to apply theoretical knowledge in practice. Mentorship, which is essential in medical education, can significantly benefit medical residents. Mentorship offers emotional and social support, aids in adaptation to new learning environments, and fosters professional advancement. Therefore, this brief report aims to provide support by focusing on the educational, skill-based, and social issues faced by residents. Materials and Methods: In 2022, a quasi-experimental study was conducted at the Shahid Beheshti University in Iran, involving 44 psychiatry residents. Seven mentors were selected from their faculty. The intervention, lasting two terms, was implemented in seven steps. Data were collected by a questionnaire and analyzed using the Statistical Package for the Social Sciences (SPSS) v. 24, with Chi-square and paired-sample t-tests applied. Results: Before training, there were no significant differences in the mean scores of the desired variables (P > 0.05). However, after training, there was an increase in the mean scores of most variables in the intervention group, including residents’ educational, skill, and social issues. The training helped residents acquire necessary skills, cope with pressures, and establish good relationships (P > 0.05). Exceptions were three items—workplace different with the mentor, random selection of mentors and residents, and interference with other mentor programs—which did not show significant change (P > 0.05). Conclusions: Mentorship programs can effectively address residents’ educational, skill, social, and health issues by helping them acquire the necessary skills, cope with pressures, and establish good relationships. The success of these programs depends on factors, such as the quality of the mentor-resident relationship, program structure and support, and the resident’s ability to utilize learning opportunities for overall well-being. The results of this study should be shared with policymakers for future planning for this group.